Analisis Jalur: Faktor-faktor yang Mempengaruhi Perilaku Pencegahan Stunting Menggunakan Health Promotion Model: Path Analysis: Factors Affecting Stunting Prevention Behavior Using The Health Promotion Model - Valentina Dili Ariwati; Qonitah Khalda (Journal of Health, 2023)
Stunting is a chronic malnutrition problem that results in irreversible growth disturbances in toddlers. Maternal factors that occur during pregnancy and after the child is born are one of the causes of stunting. This study aims to analyze the association between maternal factors that influence stunting prevention behavior using the Health Promotion Model. The research uses an analytic survey with a cross-sectional design, which was conducted in RW-4 Curug Village, Depok City. The number of samples is 110, using purposive sampling. The data analysis used is path analysis with STATA 17. The results showed that there’s a direct and positive association between perceived benefit and stunting prevention behavior (b = 1.45; p = 0.036). There’s a direct and positive association between self-efficacy and stunting prevention behavior (b= 1.83; p < 0.001). There’s an indirect and positive association between prior related behavior and stunting prevention behavior through perceived benefit (b = 1.45; p = 0.003). There’s an indirect and positive association between prior related behavior and stunting prevention behavior through self-efficacy (b = 1.78; p < 0.001). There’s an indirect and positive association between personal psychology and stunting prevention behavior through perceived benefit (b = 1.53; p = 0.001). There’s an indirect and positive association between personal psychology and stunting prevention behavior through self-efficacy (b = 1.54; p = 0.001). The factors in the health promotion model have a significant and positive association with stunting prevention behavior.